Marking Crocodiles for Release Back into the Wild for Subsequent Identification - Bustard, H. R.; Choudhury, B. C. (Indian Forester, 1981)
A permanent marking method is described to identify crocodiles being rehabilitated back into the Wild. The method involves mutilation marking-clipping the enlarged dorsal scales (scutes) on the tail. This method is simple, requiring no specialised equipment and it is easy to identify released crocodiles in the field using binoculars. A noted advantage is that the crocodilian does not need to be recaptured for positive identification to be made if it is a released crocodilian. This method has now had more than 4 years of continuous field testing in India and subordinate personnel are able to participate freely in recording sightings.